2022
DOI: 10.1007/s12671-022-01982-9
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic Process of Change During Participation in the Parents Under Pressure Program for a Cohort of Parents Who Misuse Substances

Abstract: Objectives Despite a large evaluation literature for interventions aiming to improve the lives of families affected by parent substance misuse, very few studies have examined how families change when engaged with treatment. This study examines the interactive process of change in parent psychopathology and mindful parenting during participation in the Parents under Pressure (PuP) program for parents engaged in community addiction services. Methods Parents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 85 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…The presence of clinically significant levels of parental psychopathology symptoms seems to be a clear predictor of greater difficulties in adopting a mindful parenting approach [12][13][14]. For instance, Moreira and Canavarro [13] found that mothers of adolescents with clinically significant levels of anxiety and/or depressive symptomatology had lower levels of all mindful parenting dimensions than mothers without significant levels of anxiety and/or depressive symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of clinically significant levels of parental psychopathology symptoms seems to be a clear predictor of greater difficulties in adopting a mindful parenting approach [12][13][14]. For instance, Moreira and Canavarro [13] found that mothers of adolescents with clinically significant levels of anxiety and/or depressive symptomatology had lower levels of all mindful parenting dimensions than mothers without significant levels of anxiety and/or depressive symptomatology.…”
Section: Introductionmentioning
confidence: 99%